PPIs Are Not Responsible for Elevating Cardiovascular Risk in Patients on Clopidogrel—A Systematic Review and Meta-Analysis - Demcsák, Alexandra; Lantos, Tamás; Bálint, Emese Réka; Hartmann, Petra; Vincze, Áron; Bajor, Judit; Czopf, László; Alizadeh, Hussain; Gyöngyi, Zoltán; Márta, Katalin; Mikó, Alexandra; Szakács, Zsolt; et al. (Frontiers in Physiology, 2018)
Background: Clopidogrel and proton pump inhibitors (PPIs) are metabolized by cytochrome P450 enzymes. Contradictory results have been reported on possible complications of simultaneous PPI and clopidogrel use. Our aim was to investigate the clinical relevance of this debate with a systematic review and meta-analysis. Methods: The PubMed, Embase and Cochrane Central Register of Controlled Trials electronic databases were searched for human studies (randomized controlled trials (RCTs) and observational studies) using the PICO format (P: patients on clopidogrel; I: patients treated with PPI; C: patients without PPI treatment; O: cardiovascular risk). We screened eligible studies from 2009 to 2016. After study exclusions, we extracted data from 27 articles for three outcomes: major adverse cardiac event (MACE), myocardial infarction (MI) and cardiovascular (CV) death. The meta-analysis was registered on PROSPERO (CRD42017054316). Results: Data were extracted on 156,823 patients from the 27 trials included (MACE: 23, CV death: 10, MI: 14). The risks of MACE (RR=1.22, 95% CI=1.06–1.396, p=0.004) and MI (RR=1.43, 95% CI=1.24–1.66, p<0.001) were significantly higher in the PPI plus clopidogrel group. However, subgroup analysis demonstrated that this significance disappeared in RCTs (RR=0.99, 95% CI=0.76–1.28, p=0.93) in the MACE outcome group. There was no effect of combined PPI and clopidogrel therapy on CV death outcome (RR=1.21, 95% CI=0.97–1.50, p=0.09). Conclusion: Concomitant use of PPIs and clopidogrel has been proved not to be associated with elevated cardiovascular risks according to RCTs. Based on our results, no restrictions should be applied whenever PPIs and clopidogrel are administered simultaneously.